Instability Analysis Study of the Jeffrey Nanofluid Flow through a Brinkman-Darcy Porous Medium - Devi, Promila; Rana, Gian C.; Sharma, Sita Ram; Kumar, Sanjeev (Iraqi Journal of Science, 2024)
The analysis of thermal instability in a Brinkman-Darcy Jeffrey nanofluid flow through a porous medium is studied in this paper. The nanoparticles are immersed in the Jeffrey fluid so that the thermal conductivity of the system is maintained and high medium porosity is to be undertaken. Under the impact of the Jeffrey, nanoparticles and Brinkman-Darcy parameters, the momentum-balance equations of fluid flow are mutated. The dispersion relation for the Rayleigh number is derived by employing the normal mode analysis method and linear stability theory in terms of different parameters affecting the stability of the system. It is noticed that the Darcy-Brinkman number advances the convection while the Jeffrey parameter postpones the convection in a stationary mode. To verify the results numerically, graphs have been plotted by using Origin 6.1 software. Further, for the top-heavy nanoparticles distribution, oscillatory convection does not exist.